2017
DOI: 10.1172/jci87880
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factor NFAT5 promotes macrophage survival in rheumatoid arthritis

Abstract: Defective apoptotic death of activated macrophages has been implicated in the pathogenesis of rheumatoid arthritis (RA). However, the molecular signatures defining apoptotic resistance of RA macrophages are not fully understood. Here, global transcriptome profiling of RA macrophages revealed that the osmoprotective transcription factor nuclear factor of activated T cells 5 (NFAT5) critically regulates diverse pathologic processes in synovial macrophages including the cell cycle, apoptosis, and proliferation. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
97
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(98 citation statements)
references
References 48 publications
1
97
0
Order By: Relevance
“…In macrophages (MΦs), NFAT5 mediated its activation, migration, and homeostatic regulatory function [50-52]. A high-salt diet stimulated the accumulation of MΦs in the skin, and MΦs regulated tegmental Na + Clearance in the interstitium via the function of VEGFC/ VEGFR3 and transports of Na + by stimulating the activation of NFAT5.…”
Section: The Function Of Nfat5mentioning
confidence: 99%
See 2 more Smart Citations
“…In macrophages (MΦs), NFAT5 mediated its activation, migration, and homeostatic regulatory function [50-52]. A high-salt diet stimulated the accumulation of MΦs in the skin, and MΦs regulated tegmental Na + Clearance in the interstitium via the function of VEGFC/ VEGFR3 and transports of Na + by stimulating the activation of NFAT5.…”
Section: The Function Of Nfat5mentioning
confidence: 99%
“…In several pathologic conditions, NFAT5 exacerbated the formation of damage regions. A lack of NFAT5 retarded the pathogenesis of atherosclerosis by declining the accumulation of MΦs in atherosclerotic lesions [54], and reduced the severity of arthritis with impaired inflammatory cell infiltration by inhibiting the secretion of C-C motif ligand 2 (CCL2) [50], joint destruction, and synovial hyperplasia [55]. NFAT5 also affected cancer proliferation and metastasis by enhancing protumor MΦ2 differentiation [56].…”
Section: The Function Of Nfat5mentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, it has been reported that Mac1 + cells are increased in bone marrow in old mice. Others have reported no difference in number, size, or Mac1 expression during macrophage maturation in old mice [36]. Further investigation of the impact of ageing on macrophage differentiation is needed in light of the recent advances in understanding of macrophage differentiation.…”
Section: Macrophage Polarization and Differentiation In Aging Processmentioning
confidence: 97%
“…Furthermore, steroid induce the M2 state, and DMARDs such as methotrexate and leflunomide induce M2 state as well; moreover, they impede cell replication and recruitment of immature and inflammatory monocytes to the sites of inflammation [34]. Recently, Choi and colleagues [35] reported that proinflammatory M1-polarizing stimuli and hypoxic conditions induces nuclear factor of activated T-cells 5 (NFAT 5) expression so that enhances chronic arthritis by conferring apoptotic resistance to activated macrophages. Recent animal study reported the therapeutic efficacy in rheumatoid arthritis by targeting macrophage polarization by systemic delivery of human umbilical cord blood-derived mesenchymal stem cells (hUCB-MSCs).…”
Section: Macrophages and Rheumatoid Arthritismentioning
confidence: 99%